1998
DOI: 10.1021/jo981385v
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Terpenes with Novel Carbon Skeletons from the West Indian Sea Whip Pseudopterogorgia elisabethae (Octocorallia)1

Abstract: From the hexane solubles of the West Indian gorgonian Pseudopterogorgia elisabethae collected near San Andrés Island, Colombia, were isolated a marine diterpenoid, two nor-diterpenoids, and a bisnor-diterpenoid, all of which possess most unusual carbocyclic skeletons. The structures and relative configurations of novel metabolites elisabethins A-C (1-3) and elisabanolide (4) were elucidated by interpretation of overall spectral data, which included 2D NMR correlation methods; IR, UV, and accurate mass measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
95
0
10

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 18 publications
1
95
0
10
Order By: Relevance
“…11.2 Hz, 9-H) indicated that 4 possessed the same elisabethane skeleton as found in the prototype metabolite elisabethin A (10). [10] Information gleaned from 1 H-1 H COSY, NOESY, HMQC, and HMBC spectra led to the formulation of structure 4 for elisabethin A acetate, and this was confirmed by direct conversion of 10 (previously isolated in this laboratory) to 4 upon acetylation.…”
Section: Resultsmentioning
confidence: 67%
“…11.2 Hz, 9-H) indicated that 4 possessed the same elisabethane skeleton as found in the prototype metabolite elisabethin A (10). [10] Information gleaned from 1 H-1 H COSY, NOESY, HMQC, and HMBC spectra led to the formulation of structure 4 for elisabethin A acetate, and this was confirmed by direct conversion of 10 (previously isolated in this laboratory) to 4 upon acetylation.…”
Section: Resultsmentioning
confidence: 67%
“…Ein Vergleich der 13 C-NMR-Daten von natürli-chem Elisabethin A [1] mit denen des Endprodukts der Synthese, das man aus 10 durch Hydrierung der endocyclischen C4-C5-Alkengruppierung, baseninduzierter Epimerisierung und Demethylierung in mäßiger Gesamtausbeute erhält, zeigt mehrere signifikante Abweichungen der chemischen Verschiebungen (bis zu 0.5 ppm). Darüber hi- Nach dem Einbau der Z,E-DienylGruppierung mithilfe einer NegishiKupplung des Z-Bromalkens 14 mit (E)-1-Brompropen setzten auch Rawal et al auf die hohe Stereospezifität einer IMDA-Reaktion zur Festlegung der Konfiguration der restlichen vier stereogenen Zentren.…”
Section: Methodsunclassified
“…Elisabethane fallen unter diesen Diterpenoiden wegen ihrer interessanten entzündungshemmenden, antibakteriellen, analgetischen und cytotoxischen Eigenschaften auf. Die komplizierte Struktur von Elisabethin A (1), einem repräsen-tativen Mitglied dieser Familie, dessen biologische Eigenschaften bis jetzt noch nicht vollständig untersucht sind, [1] stellt Synthesechemiker vor eine schwierige Aufgabe. Seine Struktur wurde durch umfassende spektroskopische Untersuchungen und Röntgenstrukturanalyse aufgeklärt, die aber die Bestimmung der absoluten Konfiguration dieses Naturstoffs nicht ermöglichten.…”
unclassified
See 1 more Smart Citation
“…The structure of elisabethin A 50, which was also named elisabethane, was established by spectroscopic methods and confirmed by an X-ray diffraction experiment, which also yielded its relative stereochemistry [59]. However, the absolute configuration of this molecule was not determined by the X-ray experiment, being accomplished only by their total synthesis [60].…”
Section: Stereochemistrymentioning
confidence: 98%